Collective Phenomena in Synchrotron Radiation Sources Prediction, Diagnostics, Countermeasures - Khan, Shaukat (Particle Acceleration and Detection,, 2006)
This book helps to dispel the notion that collective phenomena, which have become increasingly important in modern storage rings, are an obscure and inaccessible topic. Despite an emphasis on synchrotron light sources, the basic concepts presented here are valid for other facilities as well. Graduate students, scientists and engineers working in an accelerator environment will find this to be a systematic exposition of the principles behind collective instabilities and lifetime-limiting effects. Experimental methods to identify and characterize collective effects are also surveyed. Among other measures to improve the performance of a projected or existing facility, a detailed account of feedback control of instabilities is given.